2017
DOI: 10.1242/dev.143578
|View full text |Cite
|
Sign up to set email alerts
|

FGF and canonical Wnt signaling cooperate to induce paraxial mesoderm from tailbud neuromesodermal progenitors through regulation of a two-step epithelial to mesenchymal transition

Abstract: Mesoderm induction begins during gastrulation. Recent evidence from several vertebrate species indicates that mesoderm induction continues after gastrulation in neuromesodermal progenitors (NMPs) within the posteriormost embryonic structure, the tailbud. It is unclear to what extent the molecular mechanisms of mesoderm induction are conserved between gastrula and post-gastrula stages of development. Fibroblast growth factor (FGF) signaling is required for mesoderm induction during gastrulation through positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
95
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 80 publications
2
95
0
Order By: Relevance
“…A study in differentiating human ES cells also showed that FGF can efficiently induce expression of spinal cord markers in the absence of Wnt signaling [64]. Interestingly, at later stages of tailbud formation in the most posterior embryo regions, FGF and BMP were shown to be necessary for spinal cord formation in both zebrafish [31,65] and Xenopus embryos [66,67]. Canonical Wnt signaling was important for promoting mesoderm progenitor cells, but not neural progenitors in the posterior spinal cord [31].…”
Section: Discussionmentioning
confidence: 99%
“…A study in differentiating human ES cells also showed that FGF can efficiently induce expression of spinal cord markers in the absence of Wnt signaling [64]. Interestingly, at later stages of tailbud formation in the most posterior embryo regions, FGF and BMP were shown to be necessary for spinal cord formation in both zebrafish [31,65] and Xenopus embryos [66,67]. Canonical Wnt signaling was important for promoting mesoderm progenitor cells, but not neural progenitors in the posterior spinal cord [31].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, co-expression of master regulators of mesoderm (T) and neural (Sox2) development fits well with the proposed potency of the dual-fated progenitors. Based on this assumption, T/Sox2 double-positive cells have been studied extensively in vitro [12][13][14][15] and in vivo 6,9,11,[16][17][18][19][20] . Despite the increasing interest in NMPs, their precise role in embryonic development still remains to be elucidated, though it is hypothesized that they are essential for body axis elongation 2,9,12,16,[20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…The EMT creates a pool of disorganized mesodermal progenitors in the medial tailbud that then segregate in a bilaterally symmetric manner into the paraxial mesoderm. In zebrafish, Wnt signaling regulates the first step in this EMT (Goto et al, 2017). Thus, over-expression of the Wnt inhibitor notum1a likely increases ordered cell motion by abrogating this EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Trunk elongation involves the collective movement and proliferation of cells within the posterior edge of the embryo in a structure called the tailbud (Kanki and Ho, 1997; Lawton et al, 2013; McMillen and Holley, 2015; Quesada-Hernandez et al, 2010; Steventon et al, 2016; Wilson et al, 2009; Zhang et al, 2008) (Figure 1A, highlighted region). Throughout trunk elongation in the mouse, zebrafish and chick, a subset of prospective mesodermal cells undergo epithelial-to-mesenchymal transition (EMT) joining a pool of disordered mesenchymal progenitors that sort symmetrically into the paraxial mesoderm, which later develops into the skeletal muscle and vertebral column (Goto et al, 2017; Manning and Kimelman, 2015; Ohta et al, 2007; Wilson and Beddington, 1996). In zebrafish, this is a two-step EMT, with the first step regulated by Wnt signaling, and the second step regulated by Fgf signaling (Goto et al, 2017; Manning and Kimelman, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation